MTOR Inhibitors as a New Therapeutic Strategy in Treatment Resistant Epilepsy in Hemimegalencephaly: A Case Report. (March 2019) - Xu, Qi; Uliel-Sibony, Shimrit; Dunham, Christopher; Sarnat, Harvey; Flores-Sarnat, Laura; Brunga, Ledia; Davidson, Scott; Lo, Winnie; Shlien, Adam; Connolly, Mary; Boelman, Cyrus; Datta, Anita
Hemimegalencephaly is a hamartomatous malformation of one hemisphere. Functional hemispherectomy, the definitive treatment, is associated with significant morbidity and mortality in early infancy. Dysregulation of the mTOR pathway can result in malformations of cortical development, and mTOR inhibitors can effectively reduce seizures in tuberous sclerosis complex. We report a 6-day-old female with hemimegalencephaly and frequent seizures despite 9 antiseizure medications. At 3 months of age, while awaiting hemispherectomy, an mTOR inhibitor, rapamycin, was initiated by the neurologist. After 1 week of treatment, there was >50% reduction in seizures and total seizure burden, and after 2 weeks, development improved, resulting in deferral of surgery by 2.5 months with an increased body weight. Pathology demonstrated cortical dysplasia with upregulation of the mTOR pathway. Deep-sequencing of brain tissue demonstrated 16% mosaicism for a pathogenic de novo MTOR gene mutation. This case exemplifies how mTOR inhibitors could be considered for seizure reduction in patients with hemimegalencephaly while awaiting surgery.